A Case Study Assessing the Integration of Nuclear Safety and Security in Facilities using a Monte Carlo Simulation aided Analytical Hierarchy Process - Theodore A Thomas; Shraddha Rane; Jason Timothy Harris (International Journal of Nuclear Security, 2024)
Nuclear safety and security are essential in all operations using nuclear and radioactive materials. Even though both elements are important, the evolution of these programs has not developed at the same rate. As such, their integration has been met with challenges. This study analyzed the potential for synergy across different criteria and settings when integrating nuclear safety and security. The criteria included eight points where overlap could be identified between nuclear safety and security. Three work settings—industrial, medical, and research—were evaluated. Responses were collected from nine individuals who worked with nuclear materials in various capacities and different nuclear work settings. The individuals rated the eight criteria and three work settings based on the analytical hierarchy process. These results were then used in a Monte Carlo simulation that applied a beta-program evaluation review technique distribution to determine points with the greatest potential for synergy. The culture criterion was rated as having the greatest potential for synergy, thereby indicating that the integration of nuclear safety and nuclear security would provide the greatest benefit with this criterion. The analytical hierarchy process assisted with the Monte Carlo simulation and determined that the industrial setting ranked the highest in synergy potential—also indicating this setting would see the greatest benefit in integrating nuclear safety and security.
Keywords: analytical hierarchy process; nuclear security; nuclear safety; Monte Carlo simulation; integration